Algorithm for selecting alternative strategiesfor sustainable intensification of agricultural enterprises - Strapchuk, Svitlana І.; Mykolenko, Olena P.; Страпчук, Світлана Іванівна; Миколенко, Олена Петрівна (My University, 2022)
Growing food shortage encourage businesses to increase yields, mainly through extensive capacity building. However, this path often leads to a negative impact on the environment and does not consider social issues. Increasing yields requires the implementation of strategies for sustainable agricultural development and intensification of production. Selecting such strategies at the level of agricultural enterprises requires their classification and analysis. The purpose of the study is to group agrarian enterprises in Kharkiv Oblast and identify clusters with high potential for the implementation of alternative strategies for sustainable intensification. Based on the concept proposed by J. Pretty, the study classifies enterprises by the ecological and economic, socio-economic and environmental dimensions on the basis of such factors as crop diversity, depreciation, organic fertiliser application, labour costs, use of mineral fertilisers, fuel materials per hectare of land. Data from 514 agricultural production enterprises in Kharkiv Oblast in 2019 and 510 enterprises in 2020 were used for the categorisation. The data were processed through a cluster analysis method using specialised Microsoft Excel and SPSS21 software. The study presents an algorithm for choosing strategies for sustainable development and sustainable intensification of agricultural enterprises based on cluster analysis. Classification of enterprises by the level of diversity of agricultural crops, application of organic fertilisers, labour costs, application of mineral fertilisers, depreciation level, fuel materials per hectare of land allowed identifying agricultural enterprises that have the greatest potential to implement sustainable intensification practices from the proposed alternatives. The introduction of integrated pest management tools has been suggested for companies that consume significant amounts of mineral fertilisers and fuels and lubricants. The practical significance of the findings lies in providing recommendations for selecting sustainable intensification strategies depending on the level of enterprise yields, the amount of mineral fertiliser and fuel and lubricants used, the diversity of crops, etc. Зростаючі потреби у продуктах харчування спонукають підприємства до збільшення урожайності, здебільшого за рахунок екстенсивного нарощування потенціалу. Проте такий шлях нерідко призводить до негативного впливу на навколишнє середовище та не враховує соціальні проблеми. Збільшення врожайності потребує імплементації стратегій сталого розвитку сільського господарства та сталої інтенсифікації виробництва. Обрання таких стратегій на рівні аграрних підприємств вимагає їх класифікації та аналізу. Метою дослідження є групування аграрних підприємств Харківської області та виокремлення кластерів з найвищим потенціалом до впровадження альтернативних стратегій сталої інтенсифікації. Спираючись на концепцію, запропоновану Дж. Претті, в дослідженні було здійснено класифікацію підприємств у еколого-економічному, соціально-економічному та екологічному вимірах за такими факторами, як: рівень різноманіття сільськогосподарських культур, амортизації, внесення органічних добрив, витрати на оплату праці, застосування мінеральних добрив, паливних матеріалів на 1 га площі землі. Для групування було використано дані 514 підприємств Харківської області у 2019 році та 510 підприємств у 2020 році, що вирощували сільськогосподарську продукцію. За допомогою методу кластерного аналізу здійснено обробку даних з використанням спеціалізованих програм Microsoft Excel та SPSS21. У роботі представлено алгоритм обрання стратегій сталого розвитку та сталої інтенсифікації аграрних підприємств, спираючись на кластерний аналіз. Класифікація підприємств за рівнем різноманіття сільськогосподарських культур, внесення органічних добрив, витрат на оплату праці, застосування мінеральних добрив, рівня амортизації, використання паливних матеріалів на 1 га площі землі дозволила виокремити аграрні підприємства, що мають найбільший потенціал до впровадження практик сталої інтенсифікації із запропонованих альтернатив. Для підприємств, які споживають значні обсяги мінеральних добрив та паливно-мастильних матеріалів, запропоновано впровадження інструментів інтегрованого pest-менеджменту. Практична значущість отриманих результатів полягає у наданні пропозицій щодо вибору стратегій сталої інтенсифікації виробництва в залежності від рівня урожайності підприємств, обсягів застосування мінеральних добрив та паливно-мастильних матеріалів, різноманіття сільськогосподарських культур тощо.
Алгоритм вибору альтернативних стратегій сталої інтенсифікації аграрних підприємств
Svitlana І. Strapchuk - corresponding author
Keywords: Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING; sustainable development; sustainable development strategies; cluster analysis; one-way ANOVA; agriculture; Kharkiv Oblast; сталий розвиток; стратегії сталого розвитку; кластерний аналіз; одностороння ANOVA; сільське господарство; Харківська область